Metagenome-Assembled Genomes From Pyropia haitanensis Microbiome Provide Insights Into the Potential Metabolic Functions to the Seaweed - Wang, Junhao; Tang, Xianghai; Mo, Zhaolan; Mao, Yunxiang (Frontiers in Microbiology, 2022)
Pyropia is an economically important edible red alga worldwide. The aquaculture industry and Pyropia production have grown considerably in recent decades. Microbial communities inhabit the algal surface and produce a variety of compounds that can influence host adaptation. Previous studies on the Pyropia microbiome were focused on the microbial components or the function of specific microbial lineages, which frequently exclude metabolic information and contained only a small fraction of the overall community. Here, we performed a genome-centric analysis to study the metabolic potential of the Pyropia haitanensis phycosphere bacteria. We reconstructed 202 unique metagenome-assembled genomes (MAGs) comprising all major taxa present within the P. haitanensis microbiome. The addition of MAGs to the genome tree containing all publicly available Pyropia-associated microorganisms increased the phylogenetic diversity by 50% within the bacteria. Metabolic reconstruction of the MAGs showed functional redundancy across taxa for pathways including nitrate reduction, taurine metabolism, organophosphorus and 1-aminocyclopropane-1-carboxylate degradation, auxin, and vitamin B12 synthesis. Some microbial functions, such as auxin and vitamin B12 synthesis, that were previously assigned to a few Pyropia-associated microorganisms were distributed across the diverse epiphytic taxa. Other metabolic pathways, such as ammonia oxidation, denitrification, and sulfide oxidation, were confined to specific keystone taxa.